(3eYLes - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s
(3ChdgG (B:s
(3ef eGOI (B" (3ReLQ (B" (3, bhdg (B: (3ReLQ GdReLQI GdUhJ jbGd ddQLd EPG GcKQ GdUHGM hGdRLQ s
(3BNQgG (B:s
(3ef eGOI (B( (3RHQ (B) (3, bhdg (B: (3hGdRHQI CjVkG ehVY GdcGgd , jbGd (B: (3QLd CRHQ Ci YXje hbhdge ai GdeKd (B: (3bO gGLJ RHQGA , gi GSe LGQjI cGfJ ddCUfa Hf bjS , hcGfJ SdjWI s
(3dYdg LRA ef cJGH GdUMGM ddLhgQis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B267s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B232 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GddZIs